Controle químico de Corynespora cassiicola (Berk. & Curt.) Weir em soja - Stefanelo, Maurício Silva (2014)
Soybean target spot has become important recently, once the disease has generated economic losses to soybean producer, mainly in the Midwest. Therefore, this study aimed to evaluate alternatives managements on soybean target spot. Experiments were conducted in Canarana and Primavera do Leste, Mato Grosso State, in order to evaluate the effect of sowing date, cultivar and fungicide application programs on the severity of target spot. The application programs, that differed in the number of applications and timing of the first spraying, were tested on three soybean cultivars (TMG 7188 RR, TMG 132 RR, M-8766 RR) sown in two seasons (CHAPTER I). The efficiency of fungicides applied at different stages of the crop cycle (vegetative + reproductive, and just at reproductive stage) on cultivar TMG 7188 RR was also tested (Chapter II). Interaction betwen location and treatments was observed for severity of target spot and asiatic rust, as happened to yield. The severity of target spot was higher in the earlier sowing season, unlike soybean asiatic rust. Cultivars were differently susceptible to target spot, showing that choosing cultivar may be a disease management option. Fungicide application at vegetative stage only increased the control of target spot for TMG 132 RR sown in first sowing season in Primavera do Leste. The use of fungicides containing the molecule Fluxapyroxad were more efficient in target spot controlling, regardless of the number of sprays. The correct choice of fungicide, sowing season and less susceptible cultivars are factors to be considered in the management of the target spot in soybean.